PSYCHOANALYTIC LITERARY CRITICISM AND NAGA FOLKLORE: AN INTERDISCIPLINARY STUDY WITH REFERENCE TO TEMSULA AO - Ayeh, Nathanael (International Journal of Research -GRANTHAALAYAH, 2024)
This paper examines the integration and application of psychoanalytic literary criticism within specific folklore in Nagaland, India. The framework for analysing Ao-Naga cultural narratives from a psychoanalytical perspective is derived from a combination of models present in Temsula Ao’s The Ao-Naga Oral Tradition and Freudian constructs. Further expanding upon this concept of psychoanalytic literary criticism situates the study of folklore within specific parameters of Naga consciousness. Such application of psychoanalytic literary criticism makes it possible to visualize its scope and limitations regarding Naga folklore and folkloristics, while also focusing on oral tradition and its manifestation in literature. Temsula Ao’s The Ao-Naga Oral Tradition provides essential analysis of myths such as Lungterok (origin of the Ao-Naga ancestors from six stones). Here, Temsula Ao critiques the limitations of Western models, proposing that Naga folklore transcends conventional narrative structures to embody the collective psyche, cultural identity and legacy of its people through memories and oral tradition This study addresses the challenges of applying psychoanalytic literary criticism to folklore studies, highlighting its divergence from conventional/canonical literature due to the absence of distinct authorship and its open-ended narrative structure. By juxtaposing psychoanalytic theory with oral traditions, it reveals how the subconscious dynamics of storytelling contribute to the formation and distribution of folklore within Naga communities.